2018
DOI: 10.1021/acschemneuro.8b00298
|View full text |Cite
|
Sign up to set email alerts
|

Resident Microglia Activate before Peripheral Monocyte Infiltration and p75NTR Blockade Reduces Microglial Activation and Early Brain Injury after Subarachnoid Hemorrhage

Abstract: Early brain injury (EBI) after aneurysmal subarachnoid hemorrhage (SAH) contributes to high morbidity and mortality. Although it is well recognized that acute neuroinflammation reaction is one of the most important triggers of EBI, pharmacotherapy proved to be clinically effective against the initiating of neuroinflammation after SAH is lacking. The resident microglia and infiltrated peripheral monocyte are two main types of immune cells in central nervous system (CNS) and control the inflammation process in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…Consistent with this, we found that aneurysm rupture and high levels of sST2 after rupture were associated with shifts in immune cell populations. Our comparison between SAH patients and control patients undergoing elective aneurysm clipping found an apparent shift in a CD14 + monocyte population, which is consistent with animal studies of SAH . Human studies have similarly shown increases in monocyte‐associated genes after aneurysm rupture, elevations in monocyte chemoattractant protein 1 in serum and CSF after SAH, and increase in activated monocytes identified by CSF and peripheral blood flow cytometry .…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this, we found that aneurysm rupture and high levels of sST2 after rupture were associated with shifts in immune cell populations. Our comparison between SAH patients and control patients undergoing elective aneurysm clipping found an apparent shift in a CD14 + monocyte population, which is consistent with animal studies of SAH . Human studies have similarly shown increases in monocyte‐associated genes after aneurysm rupture, elevations in monocyte chemoattractant protein 1 in serum and CSF after SAH, and increase in activated monocytes identified by CSF and peripheral blood flow cytometry .…”
Section: Discussionsupporting
confidence: 85%
“…Brain-resident microglia cells are the first responders to central nervous system (CNS) damage; they accumulate within a short period of time in the injured area and begin the phagocytic removal of myelin debris, which is important because this debris can release axonal regrowth–inhibiting factors. Moreover, activated microglia also play an important role in glial scar formation and in support of the blood–brain barrier (BBB) (Mosley and Cuzner, 1996; Schwab, 2004; Davalos et al, 2005; Lou et al, 2016; Xu et al, 2019). However, through their TLRs, DAMPs activate the pro-inflammatory phenotype of microglia besides the early phagocytic phenotype, which is destructive to the brain tissue since it can produce pro-inflammatory cytokines, chemokines, complement system components, free radicals, and matrix metalloproteases (MMPs) which could result in an increase in BBB permeability and apoptosis (Walker et al, 1995; Jack et al, 2005; Yenari et al, 2006; del Zoppo et al, 2012; Kawabori and Yenari, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia and neutrophils are key immune cells involved in the inflammatory response in CNS inflammation-related diseases, such as hypoxicischemic brain injury and SAH (Z. Xu et al, 2019b;Yao and Kuan, 2020). FPR2, a member of the G protein-coupled receptor family, plays an important role in host defense and cellular debris clearance (Weiss and Kretschmer, 2018).…”
Section: Discussionmentioning
confidence: 99%